Students’ Learning Strategies in Public Speaking Class at Higher Education Level - Rahma Puluhulawa; Gusti Nur Hafifah; Linda Mayasari (Ahmad Dahlan Journal of English Studies, 2022)
Public speaking is the capability to speak in public with learning activities that occur through experiences and speaking practices in front of audiences. Different learning strategies the students apply in improving their speaking ability surely result in diverse speaking mastery and performances. This research aims to discover and explore what kind of learning strategies university students use in a public speaking course. Three students from the same class of public speaking course were selected as the subjects of the study. They are selected based on the score criteria: high-average score, medium-average score, and low-average score students. It was a descriptive qualitative study using questionnaires and interviews as the main instruments. The result shows that three types of students use three kinds of learning strategies: cognitive, socio-affective, and meta-cognitive strategies, but the main differences are in the factors of frequency and consistency of using the strategies. The researcher found that the high-average score student mostly used cognitive strategies to support their mastery of public speaking. The high-achieving student regularly watches and listens to English speeches on YouTube and Instagram, which cover the specific strategy: auditory representation of cognitive strategy aspects. This study concludes that the student with a high-average score employs more cognitive techniques to promote mastery of public speaking. It also recommends more frequent language exposure to improve public speaking skills.